Arte contemporânea em espaço multidisciplinar - Silva, Elaine Mathias da (2012)
This research project is aimed at delivering the outcomes of a study on the presence of contemporary works of art in multidisciplinary art exhibition spaces, and the dimensions assumed by them there. These places are unrelated to the neutrality of the white cube a term used to name spaces which are specifically set to host art exhibitions. In order to attain this goal, the development of this research paper is supported by the procedures and initiatives taken to make art exhibitions possible in the spaces previously mentioned, attempting to clarify the relational aspects that have grounded the curatorial actions as well as the artistic poetics which turned out to be part of the institutional collection. In this sense, the function that an institution can fulfill as a mediator space for art is investigated, and the circumstances where the curatorial critical position and bias adopted to select the works of art are made relevant, permeating the instances which articulate the art system: production, communication, reception. The research project is presented as a reflection on the curatorial activity that has involved artistic poetics entirely formulated in relation to multidisciplinary spaces belonging to three SESC s branches in São Paulo city, which started operating between 2010 and 2011 and have been inserting Brazilian contemporary works of art in several places which house its social cultural actions. Its purpose is to assess the art object as a factor of interaction and knowledge, as well as the institution s role in educating the audience on contemporary art.